2015
DOI: 10.1155/2015/150514
|View full text |Cite
|
Sign up to set email alerts
|

Splicing Regulators and Their Roles in Cancer Biology and Therapy

Abstract: Alternative splicing allows cells to expand the encoding potential of their genomes. In this elegant mechanism, a single gene can yield protein isoforms with even antagonistic functions depending on the cellular physiological context. Alterations in splicing regulatory factors activity in cancer cells, however, can generate an abnormal protein expression pattern that promotes growth, survival, and other processes, which are relevant to tumor biology. In this review, we discuss dysregulated alternative splicing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 129 publications
(157 reference statements)
1
26
0
Order By: Relevance
“…TQ can prevent proliferation and angiogenesis by suppressing ERK and AKT phosphorylation in human umbilical vein endothelial cells (HUVECs). The current study findings demonstrated that pERK1/2 signaling pathways were diminished by TQ (Figure 3), which was in line with previously published papers (34,35,38). Thus, additional mechanism for antiproliferative effects of TQ on PC3 cells may be applied by inhibiting pERK1/2 signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…TQ can prevent proliferation and angiogenesis by suppressing ERK and AKT phosphorylation in human umbilical vein endothelial cells (HUVECs). The current study findings demonstrated that pERK1/2 signaling pathways were diminished by TQ (Figure 3), which was in line with previously published papers (34,35,38). Thus, additional mechanism for antiproliferative effects of TQ on PC3 cells may be applied by inhibiting pERK1/2 signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, AKT is implicated in the progression of many human cancers, because it controls several factors involved in the apoptosis and cell cycle progression (33), which is in agreement with the findings of the current study. Also, ERK is a key regulatory kinase to control endothelial cell cycle, proliferation, growth, migration, and apoptosis in various types of cancers (34,35). Therefore in the current study, another possible mechanism for antiproliferative effects of TQ on PC3 cells, at least in part, can be applied by reducing pAKT signaling pathway.…”
Section: Discussionmentioning
confidence: 87%
“…At present, it has been found that there are a large number of RS domain proteins in organisms, among which about 50 species of higher organisms participate in RNA splicing [16]. The splicing factor activity of this family is regulated by reversible phosphorylation mediated by protein kinases belonging to SRPK and CLK families and by kinases activated by different signaling pathways such as MAPK, PI3K and Akt [17]. They are involved in tumor apoptosis by activating ROS and other oxidative stress pathways through interaction, and affect recurrence and metastasis [18].…”
Section: Identifcation Of Hub Genes In the Salmon Module And Darkoranmentioning
confidence: 99%
“…In summary, the major genomic and transcriptomic changes are as follows: (i) the presence of mutations in transcription factor binding and splice sites; (ii) mutations that generates aberrant proteins; (iii) different DNA arrangements and histone modifications; (iv) changes in chromatin accessibility; and (v) altered expression of splicing factors and transcription factors [6]. In the past, drugs that act on specific cellular targets were used without regard for the aberrant isoforms generated during oncogenesis, mostly due to missing information regarding the isoform variants in a gene [6,166]. The differential expression of several isoforms encoded by the same gene might be a contributing factor to the observed variation in patient responses during drug treatment [6,166].…”
Section: Therapymentioning
confidence: 99%